Pengembangan Media Pembelajaran Interaktif Berbasis Web Learning pada Mata Kuliah Rangkaian Listrik - Rahman, Hanif; Muskhir, Mukhlidi (Jurnal Pendidikan Teknik Elektro, 2025)
Many students majoring in electrical engineering do not understand electrical circuit material, causing students to have difficulty determining Ohm's law and Kirchhoff's law and resistor color codes. Therefore, one solution is to develop interactive learning media based on web learning in electrical circuit courses. This research aims to develop valid and practical learning media. This research was carried out with research and development to produce products in the form of learning media. Development models can be in the form of procedural models, conceptual models and theoretical models, procedural models are considered suitable for the development objectives to be achieved, namely to produce a product and test the feasibility of the product produced, where to achieve these objectives certain steps must be followed to produce a particular product. Based on the research carried out, it can be concluded that the development research carried out produced a valid and practical web learning-based interactive media product in the Electrical Circuits course at the Department of Electrical Engineering, Padang State University. This is proven by the validation results of interactive learning media based on web learning from two validators, that the interactive learning media developed was tested as valid. Testing the practicality of interactive learning media from lecturers' practicality is very practical, and the practicality test results are very practical. So, the development of interactive learning media based on web learning in electrical circuit courses is valid and practical.